O trabalho decente na busca pela sustentabilidade - Mattos, Michele Beutinger de (2014)
The strategic outline, political, normative and principle logical wrapped in promoting decent work is crucial in the search for effective sustainability in many of its aspects. The objective is to demonstrate that decent work understood from the working environment is part of the job that performs the strategic objectives of the International Labor Organization – ILO, namely, respect for labor rights; promoting more and better jobs; the extension of social protection; and strengthening social dialogue, and this condition produces effects of extreme relevance from the perspectives of sustainability which, in turn, is presented as a new paradigm to be attained by humanity. Thus, through literature review of works of environmental law work, labor law and environmental law, as well as various publications of the ILO, dissertations about the construction, scope of promoting decent work, describing then how sustainability has become essential for all sectors of society and human life on earth and won the multiplicity of conceptions related in the research. This way, we get the evidence that the promotion of decent work implies the realization of economic prospects, social, environmental, political and cultural sustainability. This indicates that the path to be followed by humanity in favor the realization of sustainability, the promotion of decent work is unremovable, since unemployment, informality, child and forced labor, the work without the minimum health and safety, the unequal treatment in employment and work, lack of social dialogue, and other problems that go against the decent work, produce poverty, social inequality, environmental imbalance, economic and political losses that impede sustainable world.